Analysis Of Archives Digitalization System Management In Lldikti Region Iii Jakarta - Rizki Baringbing; Marsofiyati; Ervina Maulida (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research used a qualitative descriptive method which was carried out with theaim of finding out more about the management of the archive digitization system atLLDikti Region III Jakarta. Data collection techniques use observation, interviews, and documentation and are obtained from previous research, articles, books, andw ebsites related to research on archival digitization system management.